Synthesis and characterization of epoxy polymers containing azobenzene groups that exhibit optical birefringence - Fernández, Raquél (2008)
A push-pull azo dye (DO3) was used as photosensitive substance to satisfactorily synthesize new epoxy polymers containing azo groups covalently linked. Three different amines BA, TA and MXDA were used as hardeners. Materials with different chemical structure and azo group concentration were prepared. The polymerization kinetics was followed using SEC, FTIR and DSC. It was observed that polymerization rate increases with the azo chromophore incorporation and with the photosensitive component concentration in the reaction precursors. The photoinduced birefringence of the obtained films has been analyzed. A completely reversible optical orientation was reached.